2015
DOI: 10.1016/j.bcab.2015.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular serine proteases by Acremonium sp. L1-4B isolated from Antarctica: Overproduction using cactus pear extract with response surface methodology

Abstract: Acremonium sp. L1-4B isolated from lichen in Antarctica was used to produce extracellular proteases through submerged fermentation using cactus pear extract (Opuntia ficus-indica Mill.). A 2 3 factorial design was applied to optimize the protease production using three independent variables, namely temperature, pH and concentration of yeast extract, was also used a Central Composite Design (CCD) under Response Surface Methodology (RSM). All variables and interactions analyzed in the factorial design were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Moreover, that the best production conditions were found at 35 °C using 0.25 g of wheat bran, 0.2 g of soybean meal and 0.2 g of monobasic potassium phosphate (KH 2 PO 4 ), obtaining a maximum proteolytic activity of 8.943 ± 0.220 U.mL −1 . Nascimento et al [ 23 ], working with statistical planning for the optimization of extracellular serine protease production by Acremonium sp. L1−4B, used a factorial 2 3 as the first-order planning and obtained quite different results between assays, with proteolytic activities ranging from 0.07 ± 0.01–191.32 ± 0.01 U.mL −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, that the best production conditions were found at 35 °C using 0.25 g of wheat bran, 0.2 g of soybean meal and 0.2 g of monobasic potassium phosphate (KH 2 PO 4 ), obtaining a maximum proteolytic activity of 8.943 ± 0.220 U.mL −1 . Nascimento et al [ 23 ], working with statistical planning for the optimization of extracellular serine protease production by Acremonium sp. L1−4B, used a factorial 2 3 as the first-order planning and obtained quite different results between assays, with proteolytic activities ranging from 0.07 ± 0.01–191.32 ± 0.01 U.mL −1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, even after the 24 h incubation period, the enzyme remained above 50 % of activity at 40 °C. Proteases produced by mesophilic fungi are generally denatured at temperatures above 50 °C [ 23 , 35 ]. Similar results were obtained by Areces et al [ 36 ], for the protease produced by Mucor bacilliformes , a mesophilic species, with residual activity of 29 % at 55 °C and only 8% after 30 min.…”
Section: Resultsmentioning
confidence: 99%
“…In the study reported by Turkiewicz et al [107], the serine protease secreted by Glaciozyma antarctica 107 (formerly Leucosporidium antarcticum) was most active at 25.0 C and exhibited activity even at À10.0 C. On the other hand, the serine protease purified from Acremonium sp. L1-4B was active at temperatures ranging from 10.0 to 40.0 C [82]. In another study, the protease produced by Pseudogymnoascus pannorum (formerly Geomyces pannorum) exhibited the greatest activity at 4.0 C [7].…”
Section: Proteasesmentioning
confidence: 94%
“…Antarctic fungi able to produce proteases were recovered from soil [7,12,80,99], marine invertebrates and macroalgae [18,34], melt water [12], and lichens [82]. Protease screening has been measured in solid media with skim milk, defatted milk, or casein.…”
Section: Proteasesmentioning
confidence: 99%
See 1 more Smart Citation